Calculation of band structure and optical gain of type-II GaSbBi/GaAs quantum wells using 14-band k·p Hamiltonian. (September 2017) - Mal, Indranil; Samajdar, D.P.; Das, T.D.
Abstract: The electronic band structure of strained GaSbBi/GaAs heterostructures are investigated using a 14 band k·p Hamiltonian which is an extended form of the 12 band Valance band Anticrossing (VBAC) matrix. The shift in the valence and conduction sub bands due to the incorporation of Bi in GaSb/GaAs Type II system are calculated and compared with the available experimental data. Unlike the band gap reduction of 51 meV and enhancement of spin-orbit splitting energy by ∼27 meV in bulk GaSb0.987 Bi0.013, 7.3% compressive strain in GaSbBi/GaAs quantum wells (QWs) amends the scenario completely by increasing the band gap to 1.12 eV and the spin-orbit splitting energy to 1.217 eV. The dispersion relations and effective masses of the carriers in the crystal directions Δ, Λ and Σ are calculated near the Γ point using this Hamiltonian yield some interesting results. The variation of the optical gain with the density of injected carriers and dimension of the QW is calculated and the peak of the gain curve exhibits a shift towards lower wavelengths with the decrease in the width of the QWs. Highlights: Band structure of GaSbBi/GaAs quantum wells (QWs) calculated. Generation of strain splits LH and HH sub bands. GaSbBi/GaAs QDs exhibit indirect gap type-II band alignment. Optical gain of GaSbBi/GaAs (QWs) depends on width of the well. Peak of the gain curve exhibits a shift towards lower wavelengths.